PENERAPAN MODEL PEMBELAJARAN LANGSUNG PADA PRAKTIKUM MEMBUAT DAN MENSTANDARDISASI LARUTAN DI SMK-SMTI PONTIANAK - yarso, Pratiwi; Enawaty, Eny; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The purpose of this research was to describe the competency of students’ skill in making primary solution, diluting secondary solution and standardizing solution after the researcher applied direct introduction. The sample of research was elevent grade students of Industrial Chemistry Department of SMK-SMTI Pontianak. In this research, the students consisted of 22 students. The data collection was the expertise competency assessment sheet. The result of data analysis was the primary standard solution reached the competent category (100%), the competency of the dilution of secondary standard solution reached the competent category (95%) and standardization reached the competent category (90%). Therefore, the researcher concluded that the students were competent in making and standardizing solution after the researcher applied direct introduction.Keywords: direct introduction, making solution, standardization